A Mathematically‐Tuning Model of Multicolor and White Light Upconversion in Lanthanide‐Doped ZrO2 Macroporous Matrix. Issue 12 (3rd August 2016) - Yin, Shao‐Yun; Chen, Ling; Pan , Mei; Wang, Zi; Zhang, Lu‐Yin; Wang, Hai‐Ping; Fan, Ya‐Nan; Su , Cheng‐Yong
Abstract: We present herein a fine‐tuning model for the fabrication and application of Er(III)/Tm(III)‐Yb(III) co‐doped ZrO2 macroporous matrix, which combines porosity and highly efficient multi‐color to white light upconversion photoluminescence. By control of lanthanide doping species and concentration, as well as the excitation pumping power, the emission can be tuned among red, green or blue (RGB) primary colors in a linear fashion, and trichromatically combined white light is therefore achieved. Precise mathematical matrix models are established for prediction of color chromaticity coordinates as a relation of doping composition and pumping power, which provides a general route for the development of novel upconversion materials that are particularly useful in white light displaying, multiplexed labelling and anti‐counterfeiting. Abstract : Mathematical matrix models are established for color tunable and white light upconversion macroporous ZrO2 : Er(III)/Tm(III)‐Yb(III) materials, which helps us to predicate the CIE coordinates of as‐prepared samples with different lanthanide doping composition and pumping power, and also guide the preparation and detection of samples with desired upconversion emissions.